From Green Vision to Green Action: Mediasi Green Human Resource Management pada Pengaruh Green Transformational Leadership terhadap Green Employee Involvement - Firdanita Wandira Dwi Putri Firdanita; Debi Septiani (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
The aims of this study to analyze the effect of Green Transformational Leadership on Green Employee Involvement, mediated by Green Human Resource Management (GHRM) among employees of Bank Mandiri Palembang Branch. Sustainability demands urge the banking sector to adopt eco-friendly practices, making the roles of leadership and human resource management crucial in fostering employee engagement in green initiatives. This quantitative study utilizes a survey design. The research population consists of all 85 employees of Bank Mandiri Palembang Branch, all of whom were selected as respondents through a total sampling (census) technique. Data were collected via Likert-scale questionnaires and analyzed using SEM-PLS. The results demonstrate that Green Transformational Leadership has no significant effect on Green Employee Involvement (original sample = 0.030; p-value = 0.684; H1 rejected). However, it has a positive and significant effect on GHRM (original sample = 0.450; p-value = 0.000; H2 accepted). Furthermore, GHRM has a positive and significant effect on Green Employee Involvement (original sample = 0.739; p-value = 0.000; H3 accepted). GHRM is proven to fully mediate the impact of leadership on employee involvement (specific indirect effect = 0.333; p-value = 0.000; H4 accepted). These findings confirm that green leadership is only effective when channeled through GHRM practices. This study provides theoretical contributions to green management literature and practical insights for Bank Mandiri Palembang in designing strategies to enhance employee involvement in environmental initiatives.